2022
DOI: 10.1007/s10578-022-01382-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Internalizing Symptoms During the COVID-19 Pandemic in a Transdiagnostic Sample of Youth: Exploring Mediators and Predictors

Abstract: The COVID-19 pandemic is a chronically stressful event, particularly for youth. Here, we examine (i) changes in mood and anxiety symtpoms, (ii) pandemic-related stress as a mediator of change in symptoms, and (ii) threat processing biases as a predictor of increased anxiety during the pandemic. A clinically well-characterized sample of 81 youth ages 8–18 years (M = 13.8 years, SD = 2.65; 40.7% female) including youth with affective and/or behavioral psychiatric diagnoses and youth without psychopathology compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
1
1
Order By: Relevance
“…We found that children’s depression symptom severity increased at the beginning of the pandemic, but this change was not related to the early, acute impact of COVID-19 family stressors. This finding differs from previous research showing significant associations between youth’s depression symptoms and COVID-19 stressors 8 , 34 38 . It is important to note, however, that a significant association was found between child depression symptom severity and acute COVID-19 family impacts in a sensitivity analysis in which statistical outliers were retained (see Supplementary Materials).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that children’s depression symptom severity increased at the beginning of the pandemic, but this change was not related to the early, acute impact of COVID-19 family stressors. This finding differs from previous research showing significant associations between youth’s depression symptoms and COVID-19 stressors 8 , 34 38 . It is important to note, however, that a significant association was found between child depression symptom severity and acute COVID-19 family impacts in a sensitivity analysis in which statistical outliers were retained (see Supplementary Materials).…”
Section: Discussioncontrasting
confidence: 99%
“…As predicted, the current study found that children’s anxiety symptom severity increased in the early stage of the pandemic. This finding reflects previous literature showing the prevalence of, and increases in, youth anxiety at the beginning of COVID-19 6 , 8 , 9 , 37 . Furthermore, we found that increased impact of COVID-19 family stressors heightened young children’s anxiety symptom severity at the onset of the pandemic, extending previous research in older children by showing an association between COVID-19 family stressors and anxiety symptoms during early-middle childhood 34 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation